Comunicación interna y relaciones interpersonales de los colaboradores de limpieza pública de la Municipalidad Distrital de El Porvenir, 2022 - De la Cruz Rodriguez, Lourdes Ivonne (2023)
Internal communication is a factor that influences interpersonal relationships in an entity. This research aims to analyze how internal communication influences the interpersonal relationships of public cleaning collaborators of Municipalidad Distrital El Porvenir, having as a study population 45 collaborators who belong to the already mentioned city headquarters. The present study used methods such as: inductive - deductive, analytical - synthetic and statistical, in the same way the techniques that were used are the interview and the survey, which has led to the establishment of relevant information from the points of view of the population. The instruments that have been helpful in data collection are the interview guide, interview record and questionnaire, being elementary to understand the dynamics of the variables and develop the present investigation. With the investigation carried out, it was possible to obtain as a result that communication has a positive influence on the interpersonal relationships of public cleaning collaborators of Municipalidad Distrital de El Porvenir. This can be evidenced in the commitment, dialogue and active listening among colleagues, in the same way with a high sense of belonging in their work performance and in the constant interaction with their coworkers and bosses. For this reason, it can be affirmed that in the Municipalidad Distrital de El Porvenir there is an adequate interpersonal relationship due to the favorable internal communication that exists in the areas of the organization.